2017
DOI: 10.1016/j.ejogrb.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Global variation in pregnancy complications in women with epilepsy: A meta-analysis

Abstract: There is significant variation in reported maternal and offspring outcomes in pregnant women with epilepsy across geographical regions, economic status of country and over time, which needs to be considered in setting priorities for clinical management and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Tomson et al, 11 in the EURAP Registry, report SFL in only 9.0% (632 of 7055) of pregnancies, but participants could enter the study as late as the 16th week of gestation, by which time more than 80% of SFL may occur. 11 In the prospective, rigorously monitored Women With Epilepsy: Pregnancy Outcomes and Deliveries investigation of women with epilepsy and control individuals seeking pregnancy, 9 miscarriage was reported in 12.9% of women with epilepsy and 19.7% of control individuals. If, as the EBCR findings suggest, unplanned pregnancies make up 65% of pregnancies in women with epilepsy, 2 and unplanned pregnancies in women with epilepsy carry a 2.14 risk ratio for SFL, the SFL rate of 12.9% in planned pregnancies in the WEPOD study would suggest an overall SFL rate of 22.5% in women with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Tomson et al, 11 in the EURAP Registry, report SFL in only 9.0% (632 of 7055) of pregnancies, but participants could enter the study as late as the 16th week of gestation, by which time more than 80% of SFL may occur. 11 In the prospective, rigorously monitored Women With Epilepsy: Pregnancy Outcomes and Deliveries investigation of women with epilepsy and control individuals seeking pregnancy, 9 miscarriage was reported in 12.9% of women with epilepsy and 19.7% of control individuals. If, as the EBCR findings suggest, unplanned pregnancies make up 65% of pregnancies in women with epilepsy, 2 and unplanned pregnancies in women with epilepsy carry a 2.14 risk ratio for SFL, the SFL rate of 12.9% in planned pregnancies in the WEPOD study would suggest an overall SFL rate of 22.5% in women with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis studying maternal complications in WWE presented temporal changes by comparing different geographical populations. [31] Without any reference populations, they reported an increase over time in caesarean section rates and induction of labour for WWE. We found elective caesarean section to be more frequent in WWE than in women without epilepsy, but without any increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicates a trend towards increasing rates of caesarean section and induction of labour in WWE. [31] However, different geographical populations with great variation in obstetric practice were compared to describe differences over time, and no reference populations were included. Therefore, it is not known how changes in population characteristics, obstetric practice and general complication rates have affected WWE.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found important variation exists in maternal and fetal outcomes among WWE by geographical region, economic status, and time. (Allotey, 2017) As such, our survey instrument may be useful for other future studies in LMICs as a concise tool to understand reproductive and maternal histories among WWE.…”
Section: Discussionmentioning
confidence: 99%